A grounded theory of voluntary and informal knowledge sharing. - Lee, Chu Keong. (2008)
Knowledge sharing is an essential element of organisational learning, knowledge creation, and knowledge management. It prevents the reinvention of the wheel in the organisation, ensures the spread of best practices throughout the organisation, and avails private knowledge to the problem-solving process. Unfortunately, knowledge sharing is often problematic, and has been labeled as “unnatural acts”. Research so far has surfaced two main conclusions about knowledge and people. First, knowledge is sticky in that it is stubbornly immobile, and transferring it from one person to another is often difficult and slow. Second, people are generally stubborn, refusing to share their knowledge, preferring to rely on it as their power base (the “knowledge is power” syndrome) and refusing to use knowledge that they did not create themselves (the “not invented here” syndrome).